Impact of interferon-free regimens in patients with chronic HCV and successfully ablated HCC - Amr Maged Mahmoud Rasheed; Maissa E. L. Raziky; Mohammad El Sayed; Mai Mehrez; Gamal Esmat (Egyptian Liver Journal)
Abstract Background Hepatocellular carcinoma (HCC) ranks sixth amongst all cancers and is the 2nd top cause of mortality attributable to cancer. Aim of the work This study aimed to ascertain the sustained virological response (SVR) to interferon-free regimens in chronic people with HCV after the successful treatment of hepatocellular carcinoma, as well as the percentage of persons who would demonstrate any radiological or laboratory alterations indicating a local or de novo recurrence of HCC. Patients and methods This trial was carried out on 90 Egyptian persons with chronic HCV infection who were eligible for treatment with oral antiviral agents (DAAs) with hepatic focal lesion(s). Patients were referred to from both the outpatient clinic and hepatocellular carcinoma clinic at the National Hepatology and Tropical Medicine Research Institute (NHTMRI), and the trial was conducted in the period between October 2017 and May 2021. Results Four patients with distant metastasis, three dying from liver-related incidents, received surgical resection, TACE, and RFA treatment, while one patient survived with compensated chronic liver disease. By multivariate logistic regression, we found that AFP is an independent predictor of HCC recurrence, while baseline urea level and FIB4 before antiviral therapy protect against recurrence. PLT was the best predictor, with AFP having a sensitivity of 52% and specificity of 93.8% at a cutoff value of 135 and PCR having a sensitivity of 72%. Conclusion The HCC recurrence rate was 27.8%, slightly higher than the estimated annual HCC recurrence rate following curative procedures (20%).